Active teaching strategies improve nursing knowledge and skills to assist burn victims - William Campo Meschial; Julia Rosa Matias Ciccheto; Muriel Fernanda de Lima; Jouhanna do Carmo Menegaz; Maria Elena Echevarría-Guanilo; Magda Lúcia Félix de Oliveira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to evaluate the impact of an educational intervention, on nurses' self-perception, about knowledge and skills for initial care for burn victims. Methods: a quasi-experimental study of the type before and after, with 18 nurses who assist burn victims. The intervention was carried out for 11 days in face-to-face meetings and online activities, and comprised active case-based learning strategies, simulation training, concept maps and digital portfolio. A structured instrument was used to collect sociodemographic data, and another one related to the knowledge and essential skills to the initial care for burn victims. Results: The average scores found before the intervention ranged from 2.78 to 3.33 and, after the intervention, they ranged from 3.89 to 4.72. Relevant statistical differences (p <0.005) were found in all questions addressed. Conclusion: this educational intervention, based on innovative teaching methods, showed a positive impact on nurses' knowledge and skills on initial care for people with burns.